Kekuatan Media Baru Youtube Dalam Membentuk Budaya Populer - Detya Wiryany; Tiarani Vidia Pratami (ArtComm, 2019)
Technology has never ceased to grow through time. The development itself giving a chance to new media such as Youtube to grow rapidly. Youtube is one of the largest social media that we had now. Popular culture was born from YouTube, and it’s so quickly spread by anyone who does. The Innovation Diffusion Theory developed by Everett Rogers describes how new ideas and technologies spread in culture. Basically, the Innovation Diffusion Theory explains the process of how innovation is delivered through certain channels all the time to the people from the social system. The most obvious impact that we can see today was the number of famous people that came from YouTube